Method for producing amorphous based metals - (:unkn) unknown (United States Patent, 1998)
Amorphous tungsten, cobalt, nickel, molybdenum, iron and alloys thereof can be formed by reducing metal-containing compositions to form the elemental metal wherein the particle size of the elemental metal is less than about 80 microns. This is oxidized in an oxygen-starved environment containing less than 3% oxygen and an inert gas to slowly oxidize the elemental metal. By oxidizing the metal under these conditions, the normal exotherm occurring during oxidation is avoided. The slow oxidation of the metal continues forming an amorphous metal oxide. The amorphous metal oxide can then be reacted in a reducing environment such as hydrogen to form the amorphous elemental metal. This amorphous elemental metal can then be reacted with a carburizing gas to form the carbide or ammonia gas to form the oitride or hexamethylsilane to form the silicide. This permits gas/solid reactions. The amorphous metal can also be used in a variety of different applications.
Keywords: Amorphous metal powders; Amorphous tungsten; Amorphous chromium